A New Instrument of Central Bank Policy - Whittlesey, C. R. (Quarterly Journal of Economics, 1939)
Journal Article A New Instrument of Central Bank Policy Get access C. R. Whittlesey C. R. Whittlesey Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 1_Part_1, November 1939, Pages 158–160, https://doi.org/10.1093/qje/54.1_Part_1.158 Published: 01 November 1939